Thermal inkjet printing of polyaniline on paper - Gomes, T. C. [UNESP]; Constantino, C. J. L. [UNESP]; Lopes, E. M. [UNESP]; Job, Aldo Eloizo [UNESP]; Alves, Neri [UNESP] (Elsevier B.V. Sa, 2012)
The development of organic devices requires the fabrication of thin films, and inkjet printing has been shown to be a suitable method to reach this goal. This work describes the printing process and characterisation of polyaniline (PANI) printed on bond and photographic papers using a desktop inkjet thermal printer. To enable printing, a solution composed by PANI, n-methyl-2-pyrrolidone, ethylene glycol, alcohol and water must be prepared. PANI is printed on bond and photographic paper and then doping of PANI is performed by hydrochloric acid vapour exposure. Micro-Raman spectroscopy showed that PANI printed on paper keeps its basic characteristics. The results from electrical measurements showed that the surface resistivity of the printed PANI samples decreases by increasing the printing number, i.e. the number of layers that were deposited, and depends slightly on the paper type. A stretched semicircle followed by a linear upward tail, attributed to Warburg impedance combined with other intrinsic mechanisms of PANI on porous media, are always present on the Cole-Cole plots obtained for doped-PANI on bond paper. It was shown that these parameters significantly change with the relative humidity, opening the possibility to apply PANI/paper-based devices as humidity sensors. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Polyaniline; Inkjet printing; Paper substrate; Humidity; Sensor